Smoke it to legalize! : Contributions of Ecuadorian music in the deconstruction of the hegemonic discourse on marijuana - Endara Ibarra, Fernando (2023)
The article analyzes how independent Ecuadorian music songs question the official discourse on marijuana -associated to crime and delinquency- to produce new aesthetics, politics, and ethics, around its nature and consumption, which generates collective tensions and resistance that go beyond the musical field. Methodological tools of autoethnography were used to select 5 songs: "Ojos que matan", "Sangre Cannabinol", "María (La Wirsh), "Coima", and "Santa Mariguana"; each one corresponds to a different musical genre. We analyze: 1) authorship, musicians, band's trajectory; 2) the aesthetics of the cover, clothing and performance; 3) the lyrics, especially the part that alludes to marijuana; and, 4) how these aesthetics and lyrics are interpreted as questioning the political and media truth, to provide new frameworks of interpretation to a prohibitionist discourse established in absolute truths; but which is opposed to the subjective and collective experiences of marijuana consumption in musical contexts, and, therefore, loses its objective character.